2018
DOI: 10.1016/j.ncrna.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanisms behind long noncoding RNAs and cancer

Abstract: Over the past decade, long noncoding RNAs (lncRNAs) have been identified as significant players in gene regulation. They are often differentially expressed and widely-associated with a majority of cancer types. The aberrant expression of these transcripts has been linked to tumorigenesis, metastasis, cancer stage progression and patient survival. Despite their apparent link to cancer, it has been challenging to gain a mechanistic understanding of how they contribute to cancer, partially due the difficulty in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
168
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(183 citation statements)
references
References 116 publications
(199 reference statements)
2
168
0
Order By: Relevance
“…Additionally, we showed that our gene lists contain many non-coding RNA genes, primarily consisting of lncRNAs, suggesting that methylation alterations at non-coding gene promoters are frequently present in cancer. This fits with the growing body of research showing that lncRNAs and other non-coding RNAs play a key role in cancer [30,31,32].…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, we showed that our gene lists contain many non-coding RNA genes, primarily consisting of lncRNAs, suggesting that methylation alterations at non-coding gene promoters are frequently present in cancer. This fits with the growing body of research showing that lncRNAs and other non-coding RNAs play a key role in cancer [30,31,32].…”
Section: Discussionsupporting
confidence: 83%
“…It has been suggested that lncRNAs can interact with transcriptional regulators/co-factors to form ribonucleoprotein (RNP) complexes to regulate the expression of downstream genes in the cell nucleus (40). To identify MaTAR25 interacting proteins we used two different paired sets of biotin-labeled antisense oligonucleotides targeting MaTAR25 for native RNA antisense oligonucleotide pull-down (RAP) in 4T1 cells followed by qRT-PCR which revealed a 50-60% pull-down efficiency (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High expression of HOTAIR has been implicated in various types of malignancies, and it plays a critical role in most biologic processes of cancer. 14…”
Section: Introductionmentioning
confidence: 99%